2006
DOI: 10.1177/205873920601900117
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Infiltrating Lymphocytes in Uveal Melanoma: A Link with Clinical Behavior?

Abstract: Experimental and clinical evidence indicate that immunological mechanisms might be important in the clinical course of uveal malignant melanoma (UMM). We analyzed the amount and phenotype of tumor infiltrating lymphocytes (TIL) and the expression of the apoptosis-inducing molecule Fas and its ligand, FasL, on tumor cells and TIL in a selected series of UMM with the aim to establish if a correlation between their expression and the clinical behavior of UMM exists. TIL phenotype and Fas/FasL expression were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
(48 reference statements)
1
29
0
Order By: Relevance
“…When SCs differentiate, nucleostemin expression decreases rapidly prior to cell-cycle exit both in vitro and in vivo (45). It is important to remember that HESCs are typically cultured with animal-derived "serum replacements" on mouse feeder layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When SCs differentiate, nucleostemin expression decreases rapidly prior to cell-cycle exit both in vitro and in vivo (45). It is important to remember that HESCs are typically cultured with animal-derived "serum replacements" on mouse feeder layers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that angiogenesis plays a crucial role during enchondralbone formation (44)(45)(46). Angiogenesis promotes cartilage remodeling and its transformation into bone (44).…”
Section: Differentiationmentioning
confidence: 99%
“…Conversely, T cell death, or decreased expression of TCRζ or the downstream proteins P56 lck and ZAP-70, correlates with shorter survival (51). There is also clear evidence in uveal melanoma that patients with functional CD8 + T cells have a better prognostic, whereas absence of TCRζ expression correlates with a worse outcome (52).…”
Section: Discussionmentioning
confidence: 99%
“…These concepts support the conclusion that IgE can signal the transition from inflammatory cell rolling to cell arrest [35] . We believe that there are some correlations between HUCMC-induced IL-8 and tryptase release since it has been reported that blocking tryptase reduces IL-8 significantly, a phenomenon not related with histamine production [31,[53][54][55][56] . However, more studies on IL-8 production by mast cells in vivo and in vitro are required to clarify the specificity of its proinflammatory effect.…”
Section: Discussionmentioning
confidence: 99%